Development and implementation of a simulation software for the irradiation control system in a carbon ion therapy nozzle - Jinglei Luo; Xiang Zhang; Rong Zhou; Hongda Xiao (Journal of Instrumentation, 2026)
Abstract The irradiation control system (ICS) of a carbon ion therapy nozzle is a critical component for precise beam delivery and real-time monitoring, coordinating the operational states of the accelerator, scanning magnet power supplies, and ionization chambers during irradiation. To support offline verification and debugging under non-clinical conditions, a behavioral-level verification framework for the ICS was developed. The framework integrates accelerator field-event simulation, X/Y scanning magnet power supply simulation, and ionization chamber data analysis into a unified architecture. Unlike conventional protocol-level simulators, the proposed framework reproduces the operational behaviors of external subsystems involved in irradiation control, enabling the ICS to be evaluated under both normal and abnormal operating conditions. A dual-state-machine packet-parsing strategy and a state-dependent command-processing mechanism were implemented to reproduce subsystem interactions and support offline verification of ICS operation. Experimental results demonstrate that the framework successfully verified normal command interactions and detector-data forwarding, while also reproducing representative abnormal operating conditions, including communication interruptions, invalid packet transmissions, and delayed subsystem responses. These results indicate that the proposed framework provides an effective laboratory platform for ICS functional verification, system integration testing, and subsequent debugging.